Perspectives on death and dying - Leishman, June L. (M & K Publishing, 2009)
In the past, most people encountered death at a relatively young age. Dying relatives were cared for at home, and mortality rates were higher. Today, there is much less familiarity with death, which increasingly takes place in hospitals, hospices and nursing homes. This wide-ranging and enlightening book offers an exploration of death and dying as human conditions that impact on the individual, their significant others and those involved with their care and well-being. It is aimed at medical and healthcare staff, social workers and counsellors, as well as social sciences and health psychology.